(untitled) (European Journal of Pure and Applied Mathematics, 2025)
We present a new transform called the conformable double Laplace-Shehu transform. This tool helps in solving fractional partial differential equations. These equations come up often in science and engineering. The transform is built using the idea of the conformable derivative. We explain the basic rules of the transform and show how it can be used. To show its use, we solve two equations that are well known. These are the wave and heat equations.